Selective head-neck cooling after concussion shortens return-to-play in ice hockey players - Gard, A.; Tegner, Y.; Bakhsheshi, M. F.; Marklund, N. (Concussion, 2021)
We aimed to investigate whether selective head-neck cooling could shorten recovery after sports-related concussions (SRCs). In a nonrandomized study of 15 Swedish professional ice hockey teams, 29 concussed players received immediate head and neck cooling for =30 min (initiated at 12.3 ± 9.2 min post-SRC by a portable cooling system), and 52 SRC controls received standard management. Players receiving head-neck cooling had shorter time to return-to-play than controls (7 vs 12.5 days, p < 0.0001), and 7% in the intervention group versus 25% in the control group were out of play for =3 weeks (p = 0.07). Immediate selective head-neck cooling is a promising option in the acute management of SRC that should be addressed in larger cohorts.